Unique Contextual Conditions Affecting Coworker Knowledge Sharing and Employee Innovative Work Behaviors - Imad Shah, Syed, (Colegio Oficial de Psicólogos de Madrid, 2020)
Drawing on a componential model of creativity, this study examines how coworker knowledge sharing drives employee innovative work behaviors in the workplace. Furthermore, the moderating effect of situational factor (supervisor knowledge sharing) and personal factor (employee thriving) were analyzed to explore the unique contextual conditions which could influence this relationship. A sample of 374 employees across a variety of jobs and industries was used to test these relationships. Supervisor knowledge sharing was hypothesized to dampen, while employee thriving at workplace was hypothesized to strengthen the positive relationship between coworker knowledge sharing and employee innovative work behaviors. Results of the hierarchal multiple regression, plots, and slope analysis confirmed the hypothesized relationships. The theoretical and practical implications for employee innovative work behavior at work are discussed.